An insight in the mechanism of beta sheet formation via CSAW. - Goh, Boon Chong. (2011)
Protein folding problem is an emerging eld in biophysics and great progress has been seen in experiments, theories and computations for the last 40 years. Approaching the problem with theoretical and computational studies, Conditioned Self-Avoiding Walk (CSAW) model is developed in the aim of studying the key interactions resulted in folding of a protein. The earlier versions of CSAW model consider hydrophobic interaction and hydrogen bonding while neglecting all other interactions. Though simple, these models have successfully formed hydrophobic core and alpha helix. However, none of them has consistently folded a beta sheet, the complementary secondary structure of alpha helix. In my Final Year Project, I consolidated various ideas in our research group and introduced the neighboring hydrogen bond interaction, also named as the 4-body interaction. After incorporating the 4-body interaction into CSAW, beta sheets are consistently formed. We continued to investigate the folding of polyalanine of di erent lengths and attempt to fold two real proteins in CSAW. At low temperatures, the polypeptides were folded into alpha helix while they formed beta sheet at higher temperatures. We observed as the length of protein increases, the transition temperature from alpha helix to beta sheet increases.